Paulus Melissus and Jacobus Falckenburgius: Two German Protestant Humanists at the Court of Queen Elizabeth - Piepho, Lee (The sixteenth century journal, 2007)
This article discusses two German Protestant writers who used Latin to insert themselves into the culture of the Elizabethan court. Jacobus Falckenburgius's two collections of verse indicate the strategies and, when placed within the political context of the court, the perils that a Reformed Protestant encountered in advancing his religious and political commitments. Like Falckenburgius, Paulus Melissus saw England as a safe haven from the religious wars. He used his considerable literary skills more openly to seek professional advancement at Elizabeth's court. But like Falckenburgius he too was interested in England's role in continental politics, and a series of poems to Elizabeth suggests the complexities that arose when a poet as sophisticated as Melissus tried to draw the English queen into his vision of Europe's religious and political destiny. The literary works of Falckenburgius and Melissus discussed in this article are important in contributing to a transnational Protestant literary culture that, often using Latin, connected the English court with Protestant centers in continental northern Europe.